A STUDY OF FEMINIST IDEAS IN THE POETRY OF SOUAD AL-SABAH - Farzizadeh, Zahra; Yusefi, Fatemeh; Giti, Shahriar (Gênero & Direito, 2019)
Abstract: Feminism literally means "women’s liberation"," womanism " which is itself divided into different ways. Feminism has sometimes been interpreted as organized movements for women’s rights and sometimes for the theory that believes in equality between men and women in political, economic, social and legal terms. With the spread of the feminist movement, much work was written on women, and all of them had a fixed principle that was to remove the inferiority and inequalities that had been permitted to women throughout history. With the spread of such works, feminist literature emerged. And many poets and writers have created works in this regard. Kuwaiti poet Souad al-Sabah is one of these poets. In this study, we have tried to look at feminism and its implications in terms of feminism, including patriarchy, patriarchy, women’s dependency, women’s subordination, and lack of public presence in Souad al-Sabah ’s poetry.